Yeast protein modulates metabolites derived from the human gut microbiota of older male adults ex vivo to strengthen gut barrier function and reduce inflammation - Van den Abbeele, Pieter; Vu, Lam Dai; Poppe, Jonas; van Hengel, Ingmar A. J.; Baudot, Aurélien; Zhang, Yan; Chen, Zhixian; Yan, Jun (Frontiers in Microbiology, 2026)
IntroductionThe rising global demand for protein is accelerating interest in sustainable alternatives with health benefits. While glycans are well-known for supporting gut health, the role of dietary proteins in promoting healthy aging via microbiome modulation is less understood. Yeast protein (YP) represents a sustainable, non-animal, hypoallergenic option.MethodsUsing the clinically predictive ex vivo SIFR® technology (Systemic Intestinal Fermentation Research), we examined how YP influences the microbiome of older human adults (50–65 years, n = 6), comparing its effects to whey protein isolate (WPI) and soy protein isolate (SPI).ResultsAt a dose equivalent to 40 g/day, all protein sources supported gut barrier integrity and reduced inflammation, reflected by decreased pro-inflammatory markers and increased IL-10. These benefits were linked to higher short-chain fatty acid (SCFA) production, mainly from Bacillota and Bacteroidota, including microbial markers associated with healthy aging. YP and SPI specifically restored butyrate-producing microbes and increased microbial diversity, which is linked to longevity. Untargeted metabolomics revealed numerous beneficial amino acid-derived metabolites, including indoles and polyamines, known to act through gut-organ axes to extend health span. Despite similar overall profiles, product-specific differences emerged: YP most strongly reinforced barrier integrity, produced the lowest gas levels (suggesting superior tolerability), and yielded the lowest trimethylamine N-oxide, a compound linked to increased mortality in older adults.DiscussionCollectively, these findings highlight the potential of YP as a sustainable protein source that modulates the microbiome and metabolome, reduces inflammation, and reinforces gut barrier function, which are key mechanisms for preserving health span and mitigating age-related decline.